Approaching violence against Indigenous women in the Americas from relational, intersectional and multiscalar perspectives. Issue 1 (2nd January 2020) - Guimont Marceau, Stéphane; Figueroa Romero, Dolores; Jiménez Estrada, Vivian; Rice, Roberta
ABSTRACT: The epidemic of violence against Indigenous women in the Americas reveals a broad social dynamic that crosses national and regional borders. The violence of colonization and exploitation is reproduced at different scales, from within the home to the international scene, placing Indigenous women in spaces of exclusion, at the margins of state and society, where violence can unfold and reproduce itself in total impunity. This article presents the methodology of an initiative that aimed to shed light on the endemic violence suffered by Indigenous women and on the resistance efforts, initiatives and strategies to address it. Based on a virtual forum, which was conceived of as a space of exchange between multiple voices and actors from a variety of perspectives, we highlight discussions on the politics of defining violence, the impacts of the exclusion of bodies and territories, the multifaceted strategies of resistance, as well as paths for further policy-relevant research.